Habitus, representações sociais e a construção do ser professora da educação infantil da cidade de Campina Grande - PB - Soares, Luisa de Marillac Ramos (2011)
We present here the results of a study whose objectives were to identify the social representation of being a professor of early childhood education in Campina Grande - PB, in the public state and municipal levels, and detect structural diagrams of a possible mental habitus of professorial faculty of education child, which would form the basis for the construction of this representation. As a theoretical base, we adopted the model developed by Domingos Sobrinho (1998, 2000, 2003, 2010, 2011), which articulates the Theory of Social Representations, Serge Moscovici, and the foundations and concepts of Pierre Bourdieu praxiology. It is based also on the Central Nucleus Theory, which focuses on the structural approach of social representations. Thus, puts in evidence the relational dynamics and symbolic, through which individuals come into contact, describe, understand and reproduce the outside world in his image and likeness. 199 teachers participated in the study of child care and pre-schools of Campina Grande - PB and 109 of the state. The methods and techniques used were: a) participant observation of everyday life of teachers of kindergartens and preschools, b) semi-structured interview, c) free associations of words with inducing the expression 'being a professor of early childhood education is ...' and d) semi-structured questionnaire. The data were analyzed in the case of interviews through the categorical content analysis, as proposed by Bauer (2010); free-associations, using the software Ensemble L'Analyse des Programmes Permettant evocations (EVOC), developed by Vergès (2002), which combines frequency and average order of recall (or association) and the questionnaire data, the Statistical Package for the Social Sciences (SPSS). It was verified the existence of a unique social representation shared by the population studied, but its content is structured differently. For local teachers, the centrality of the content is given by the elements commitment, dedication, responsibility, and rewarding teachers for this state revolves around the elements of love, patience, and rewarding responsibility. However, it is constructed mainly based on the related produced by a religious habitus and maternal habitus, which are part of the genesis of the establishment of professorial habitus in focus, among other cultural references of secondary influence. We conclude that a teacher of early childhood education actually researched, is materialized in the practices of educating and caring, in a clear fusion of the role of teacher and mother